Participatory 3D modelling as a socially engaging and user-useful approach in ecosystem service assessments among marginalized communities. (June 2017) - Ramirez-Gomez, Sara O.I.; Verweij, Pita; Best, Lisa; van Kanten, Rudi; Rambaldi, Giacomo; Zagt, Roderick
Abstract: Land use decision making in the Upper Suriname River area knows a history of disempowerment and marginalization of the Saamaka communities inhabiting the area. Non-recognition of land rights is at the origin of this problem. This is aggravated by the increasing over-exploitation of timber resources by powerful stakeholders and the unfair distribution of timber benefits. This has left Saamakans marginalized, causing distrust and opposition among themselves and towards outsiders. Furthermore, as a result of deforestation, Saamakans face detrimental changes in the ecosystem services (ES) that support their traditional livelihoods, with important effects for their wellbeing. This environment of distrust, opposition and marginalization makes it difficult to assess these concerns. Hence, an ES assessment approach that would generate salient ES knowledge while generating trust, communication among stakeholders and local capacity building was needed. In this paper we evaluate whether Participatory 3D modelling (P3DM) is an effective approach for ecosystem services assessments in such disenabling environments. We evaluate this by using empirical data from an ES assessment in the Saamaka region using a P3DM approach. Results show the efficient identification and evaluation of 36 ES representing provisioning, cultural and regulating service categories with crops, fish, wild meat, timber and forest medicines identified as most important. We found a decrease in the demand and supply of crops, fish and wild meat associated with ecosystem degradation, out-migration and changes in lifestyles. Further, our findings show an increasing demand and decreasing supply for timber related to over-exploitation. We provide evidence of the utility of P3DM to foster multi-functional landscape development among wary communities. Further, we discuss the usefulness of the approach and the necessary conditions needed for P3DM process to tackle the needs of the local communities as well as the need for a broader P3DM implementation strategy beyond the engagement, screening, and diagnostic phases of ES assessments when the aim is to enhance ES outcomes for marginalized communities. Highlights: An approach for ecosystem service assessment among wary communities is proposed. We effectively assessed and mapped multiple ecosystem services in a short time. The mapping method fosters a collaborative research that is socially-engaging and user-useful. We report the need to enhance access and control of the information by communities. This ecosystem services mapping approach is useful for marginalized, data-poor regions.